Optical material performances, measurement by laser implementation and interpretations - Zoran Latinović; Branka Kaluđerović; Sanja Jevtić; Stanko Ostojić; Đurđe Milanović (Zaštita Materijala)
Optical material performances along with main response functions belong to nondestructive measurements. Lasers brought new techniques beside accuracy increase. Nonlinear techniques introduced new solutions. These could be used in industry, biomedicine, and ecology with fast material description in various phases. The paper is elaborating optical characteristics in various phases and descriptions (purity, dynamics and optical breakdowns). From the scattering point of view, water represented medium, unstable when pure comparing to organic etalons. As solvent for macromolecules and polymers it is difficult to be observed. In solutions with surface active materials, the stability of the formation is important. A few aspects of experiments and scattering theories (static and dynamic) of mono and polychromatic light including nonlinear approaches were analyzed.